From conflict of discourses to military conflict: Multimodality of identity construction in Russo-Ukrainian war discourse - Ushchyna, Valentyna (East European Journal of Psycholinguistics, 2022)
This study is an attempt to grasp the discursive nature of Russo-Ukrainian war. The critical discourse analysis of the conflicting ways  Russian and Ukrainian identities are constructed in discourse and by discourse can shed light onto the covert reasons of the unprovoked military aggression Russia has been executing against Ukraine. Our assumptions are based on the idea that identity is a manifold of stances taken by individual as well as collective speakers in various situations of communication. Having epistemic and affective dimensions, stances are inherently interactive, and, thus, have a collective or social nature. Generally speaking, conflictual stances, built in war discourse, express national, political, or sociological worldviews of the stance-takers, reflecting their ideologies, values, and beliefs. The way people see the conflict differs according to what "frames" they choose to see it through. In this study, the frames circumscribing Ukrainian and Russian conflictual identities, as they are built in Ukrainian and Russian media discourse, including social media, have been deconstructed and analyzed. As there are diverse semiotic systems that are used to create, transmit and understand meanings (e.g., verbal and non-verbal, written and oral, visual and audial) various modalities employed in the process of discursive construction of these identities were taken into consideration.